Gray's anatomy the anatomical basis of clinical practice - Standring, Susan MBE, PhD, DSc, FKC, Hon FAS, Hon FRCS; Gray, Henry 1825-1861 (Elsevier, 2021)
"In 1858 Drs Henry Gray and Henry Vandyke Carter created a book for their surgical colleagues that established an enduring standard among anatomical texts. After more than 160 years of continuous publication Gray's Anatomy remains the definitive comprehensive reference on the subject offering ready access to the information you need to ensure safe effective practice. This 42nd edition has been meticulously revised and updated throughout reflecting the very latest understanding of clinical anatomy from the world's leading clinicians and biomedical scientists. The book's acclaimed lavish art programme and clear text has been further enhanced while major advances in imaging techniques and the new insights they bring are fully captured in state of the art X-ray CT MR and ultrasonic images. The accompanying eBook version is richly enhanced with additional content and media covering all the body regions cell biology development and embryogenesis - and now includes two new systems-orientated chapters. This combines to unlock a whole new level of related information and interactivity in keeping with the spirit of innovation that has characterised Gray's Anatomy since its inception."--Publisher's website